2023
DOI: 10.1186/s41983-023-00647-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, radiological and electrophysiological predictors for drug-resistant epilepsy

Abstract: Background Epilepsy is the third chronic brain illness worldwide. About a third of the epileptic patients will be drug resistant. Early identification of these patients is critical for appropriate treatment selection and prevention of the devastating consequences of recurrent seizures. The objective of this study aims to detect clinical, electrophysiological, and radiological predictors for drug-resistant epilepsy patients. Results One hundred fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…Several studies have indicated that symptomatic etiologies strongly predict drug resistance in patients with epilepsy [ 23 , 24 ], with structural etiologies being the most frequently reported in patients with DRE [ 23 , 25 ]. Similarly, in our patients with a known etiology of epilepsy, structural etiologies were the most common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that symptomatic etiologies strongly predict drug resistance in patients with epilepsy [ 23 , 24 ], with structural etiologies being the most frequently reported in patients with DRE [ 23 , 25 ]. Similarly, in our patients with a known etiology of epilepsy, structural etiologies were the most common.…”
Section: Discussionmentioning
confidence: 99%
“…EEG was available for review in approximately 80% of our patients; similar rates have been reported in the literature [ 20 ]. A study investigating electrophysiological predictors for DRE revealed that abnormal EEG findings were significantly more common in patients with DRE (69.2%) than in the well-controlled group (44.7%) [ 23 ]. In contrast, in our cohort, abnormal EEG findings were reported in only 27.5% of those who underwent EEG.…”
Section: Discussionmentioning
confidence: 99%